Small phonon contribution to the photoemission kink in the copper oxide superconductors. - Giustino, F; Cohen, M; Louie, S (2008)
Despite over two decades of intense research efforts, the origin of high-temperature superconductivity in the copper oxides remains elusive. Angle-resolved photoemission spectroscopy experiments have revealed a kink in the dispersion relations (energy versus wavevector) of electronic states in the copper oxides at binding energies of 50-80 meV, raising the hope that this anomaly could be a key to understanding high-temperature superconductivity. The kink is often interpreted in terms of interactions between the electrons and a bosonic field. Although there is no consensus on the nature of the bosons (or even whether a boson model is appropriate), both phonons and spin fluctuations have been proposed as possible candidates. Here we report first-principles calculations of the role of phonons and the electron-phonon interaction in the photoemission spectra of La(2 - x)Sr(x)CuO4. Our calculations within the standard formalism demonstrate that the phonon-induced renormalization of the electron energies and the Fermi velocity is almost one order of magnitude smaller than the effect observed in photoemission experiments. Therefore, our result rules out electron-phonon interaction in bulk La(2 - x)Sr(x)CuO4 as the exclusive origin of the measured kink. Our conclusions are consistent with those reached independently in a recent study of the related compound YBa2Cu3O7.